Using Nigerian English in an International Academic Setting - Cunningham, Una (Research in Language, 2012)
This study examines the English pronunciation of a group of Nigerian students at a university in Sweden from the point of view of their intelligibility to two groups of listeners: 1) native speakers of English who are teachers at the university; 2) nonnative speakers of English who are teachers at the university. It is found that listeners who are accustomed to interacting with international students do better than those who are not, and that native speakers of English do no better or worse than non-native listeners. The conclusion is drawn that locally useful varieties of Nigerian English may not easily be used as for wider communication and that students preparing to study abroad would find it useful to gain access to a more widely intelligible variety.